Influence of the Ionic Strength in the Intrinsic Viscosity of Xanthan Gum. An Experimental Review - Vega, Enrique D. (2015)
This study involves the influence of ionic strength in intrinsic viscosity of xanthan gum. The best concentration of monovalent and bivalent cations chloride salts is evaluated. The salt concentration is 0.001 M for monovalent cations and 3 x 10-5 M for bivalent cations and the hydrodynamic radius is maximum for these concentrations. The minimal concentration is in the range of 0.01 to 0.1 M for different cations.